THE HYPERBOLE AS A FOUNDATIONAL TOOL FOR MAGICAL REALIST ONTOLOGY OF THE NOVEL 100 YEARS OF SOLITUDE (International journal of artificial intelligence, 2026)
This paper explores the function of hyperbole not merely as a decorative rhetorical device, but as the primary ontological foundation of Gabriel Garcia Marquez's One Hundred Years of Solitude. While magical realism is often defined by the seamless integration of the supernatural into the mundane, this study argues that hyperbole serves as the linguistic bridge that collapses the distinction between the two.By analyzing key episodes such as the insomnia plague, the four-year rainfall, and the physical elevation of Remedios the Beauty the research demonstrates how Garcia Marquez utilizes quantitative and qualitative exaggeration to recalibrate the reader's perception of the possible.